Allosteric Modulation of Mitochondrial Complex I By Succinylation of NDUFV2 Subunit Under Hyperglycemic Conditions: Implications for Ros-Mediated Β-Cell Apoptosis in Type 2 Diabetes - Zainab Nasser Hussein (Universitas Negeri Malang, 2026)
Background: Type 2 diabetes mellitus is a disease of progressively dysfunctional pancreatic β-cells, including β-cell apoptosis, where mitochondrial oxidative stress is a key pathogenic factor. Nevertheless, the molecular pathway which connects chronic hyperglycemia with mitochondrial Complex I dysfunction is not fully understood. Aim: The study examined the role of hyperglycemia-induced succinylation of the NDUFV2 subunit as an allosteric modulator of mitochondrial Complex I, increased reactive oxygen species (ROS) generation, and β-cell death. Methodology: A mechanistic study was planned with the use of INS-1 β-cells under normoglycemic (5.5 mmol/L) and hyperglycemic (25 mmol/L) conditions after 48 h of incubation, with osmotic controls, antioxidant treatment, SIRT5 overexpression, and site-directed mutagenesis of NDUFV2. Immunoprecipitation, immunoblotting and LC-MS/MS were used to assess NDUFV2 succinylation, while standard mitochondrial and cell-death assays were used to measure Complex I activity, oxygen consumption, ATP production, membrane potential, ROS generation and apoptosis. Results: Hyperglycemia elevated NDUFV2 succinylation 2.71-fold, mitochondrial ROS 2.31-fold, and caspase-3/7 activity 2.87-fold, and decreased Complex I activity to 58% and ATP to 24.8 nmol/mg protein. The K81R mutant restored Complex I activity to 88%, lowered ROS to 1.34-fold, and enhanced viability to 89%. Conclusion: NDUFV2 succinylation may be one of the mechanistic causes of Complex I impairment and ROS-induced β-cell apoptosis in type 2 diabetes.